2019
DOI: 10.1080/23311886.2019.1664193
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic factors influencing smallholder farmers’ decision to participate in agro-processing industry in Gauteng province, South Africa

Abstract: Smallholder farmers in South Africa have not been linked successfully to sustainable agro-processing value chains. This study aimed to identify factors influencing smallholder farmers' decision to participate in the agro-processing industry, as well as the extent of their participation in the Gauteng Province. Data was collected through a structured questionnaire that was administered face-toface to respondents in a randomly purposive selected sample of 102 smallholder farmers. A double-hurdle model was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 12 publications
10
40
2
2
Order By: Relevance
“…Besides, this would create awareness about value addition, provide price information, and overall market conditions. This finding agrees with the results by Khoza, Senyolo, Mmbengwa, Soundy, and Sinnett, (2019) that participation decisions and intensity of value addition was negatively related with distance from the market. Additionally, the number of training on value addition positively increased the proportion of mangoes value-added by 1.72 units.…”
Section: Determinants Of the Proportion Of Mangoe Value Added Among Ssupporting
confidence: 93%
“…Besides, this would create awareness about value addition, provide price information, and overall market conditions. This finding agrees with the results by Khoza, Senyolo, Mmbengwa, Soundy, and Sinnett, (2019) that participation decisions and intensity of value addition was negatively related with distance from the market. Additionally, the number of training on value addition positively increased the proportion of mangoes value-added by 1.72 units.…”
Section: Determinants Of the Proportion Of Mangoe Value Added Among Ssupporting
confidence: 93%
“…Table 1 lists the ALVs considered for this study, common name, and the names the local used to refer to the crop. Khoza et al [29] highlighted that conditions of livelihood in the rural areas are reflected in the socioeconomic factors of households, which in turn influence the household's economic behaviour and affect market participation decisions. Table 2 indicates the socioeconomic characteristics of the 60 interviewed respondents consisting of 90% females and 10% male.…”
Section: Resultsmentioning
confidence: 99%
“…South African Government has found it challenging to transform the agro industries to include smallholder-farming entrepreneurs. Thus, Khoza et al (2019) reported that smallholder farmers in South Africa had not been linked successfully to sustainable agro-processing value chains. Currently, commercial agriculture is the leading player in the agro-processing industries in South Africa, whereas smallholder farmers play a limited role despite receiving support from the Government (Khoza et al, 2019 andMmbengwa et al, 2011).…”
Section: Contextualization Of the Studymentioning
confidence: 99%
“…Thus, Khoza et al (2019) reported that smallholder farmers in South Africa had not been linked successfully to sustainable agro-processing value chains. Currently, commercial agriculture is the leading player in the agro-processing industries in South Africa, whereas smallholder farmers play a limited role despite receiving support from the Government (Khoza et al, 2019 andMmbengwa et al, 2011). The lack of linkages to these chains had various productive and economic implications for the whole smallholder farming fraternity, including the extension advisory services whose critical roles are to advise the farmers to access opportunities in their respective commodity sub-sectors.…”
Section: Contextualization Of the Studymentioning
confidence: 99%